Uji Kualitas Tepung Jagung Alternatif dari Limbah Tongkol Jagung Menggunakan Lactobacillus casei - Mirnawati Mirnawati; Ida Ifdaliah (Al-Kimia, 2021)
Corn cobs are agricultural waste that is very widely available and has the potential to be developed as corn flour. This modified corn flour from corn cobs waste can be an alternative to flour in several flour-based processed products. The use of corn cobs, which so far has less economic value, is to conduct research to determine the quality content of corn flour and corn cobs, so it is necessary to characterize the quality of corn, especially microbial contamination based on the SNI standards that have been set.Methods: water content using gravimetric method, ash content using gravimetric method, microbial contamination test using ALT method of 25-250 colonies / gram counted and analysis of mold and E. coli bacteria. The results showed that the ash content was 0.0433%, 13.57% moisture content, 11.91% protein content, ALT 1.8 x 106, mold analysis of 4.3 x 102 cology / gram and analysis of E. coli bacteria amounting to 7.1 APM / g and B. subtilis amouting <1,0 x 102coloni/g.  So it can be concluded that corn cobs waste can be used as corn flour because it has fulfilled the SNI